The fake news pandemic in the time of the COVID-19 pandemic - Paszek, Agata; Sitko, Barbara (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
The COVID-19 pandemic was a socially significant event, but its effects and impact were also noticeable in the media world. Although various epidemics have been recorded over the years, today's one has a special character due to the fact that its effects were also noticeable in the media space, which also had an impact on the society. Today's times are characterized by highly developed technology, and the media - known as the fourth power - play a significant role in them. They also play an essential role in the context of a pandemic - primarily in connection with the flow of information on diseases or actions taken in response to the current epidemiological situation. Unfortunately, this is not only a service role, as not all messages can be considered credible. Moreover, some information is extremely harmful. The problem of fake messages is especially noticeable and, at the same time, the most disturbing one in the Internet due to the fact that all kinds of information spread very quickly in it. In this study, the authors outlined the role of fake news in the era of the coronavirus pandemic, including the definition of fake news, the ethical aspect, as well as examples with a description. The study is an overview and describes the areas affected by fake news and its consequences.